Re-evaluating the impact of alternative RNA splicing on proteomic diversity - Manuel, Jeru Manoj; Guilloy, Noé; Khatir, Inès; Roucou, Xavier; Laurent, Benoit (Frontiers in Genetics, 2023)
Alternative splicing (AS) constitutes a mechanism by which protein-coding genes and long noncoding RNA (lncRNA) genes produce more than a single mature transcript. From plants to humans, AS is a powerful process that increases transcriptome complexity. Importantly, splice variants produced from AS can potentially encode for distinct protein isoforms which can lose or gain specific domains, and hence differ in their functional properties. Advances in proteomics have shown that the proteome is indeed diverse due to the presence of numerous protein isoforms. For the past decades, with the help of advanced high-throughput technologies, numerous alternatively spliced transcripts have been identified. However, the low detection rate of protein isoforms in proteomic studies raised debatable questions on whether AS contributes to the proteome diversity and on how many AS events are really functional. We propose here to assess and discuss the impact of AS on proteomic complexity in the light of the technological progress, updated genome annotation and current scientific knowledge.